In search of the correlates of overexcitability - Martowska, Katarzyna; Matczak, Anna (Studia Psychologica: Theoria et praxis, 2016)
This article presents the results of research into the relationship between overexcitability and temperamental qualities, intelligence, emotional and social competencies, as well as well-being. The results showed that the relationships vary for different types of overexcitability, which proves that the construct is not uniform.